2013
DOI: 10.18553/jmcp.2013.19.9.745
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Decision Makers’ Use of Comparative Effectiveness Research: Report from a Series of Focus Groups

Abstract: BACKGROUND: Comparative effectiveness research (CER) is a helpful approach to improve health outcomes by developing and disseminating evidence-based information to patients, clinicians, and other decision makers about the most effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The main critiques of EPC reports in the formulary decisionmaker project that limited their effectiveness were: the reports lacked timeliness (they came out months after the new drug needed to be reviewed internally), and the results were perceived as largely inconclusive. 5 In our current project, KIs feel the timeframe from project initiation until publication of a systematic review is too long and they prefer guidelines because they have more definitive recommendations. Systematic reviews cannot be guidelines, even though quality guidelines are driven by rigorous systematic reviews.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main critiques of EPC reports in the formulary decisionmaker project that limited their effectiveness were: the reports lacked timeliness (they came out months after the new drug needed to be reviewed internally), and the results were perceived as largely inconclusive. 5 In our current project, KIs feel the timeframe from project initiation until publication of a systematic review is too long and they prefer guidelines because they have more definitive recommendations. Systematic reviews cannot be guidelines, even though quality guidelines are driven by rigorous systematic reviews.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…In an assessment of formulary decisionmakers in health-systems published in 2013, 39 pharmacists and 18 physicians on health-systems pharmacy & therapeutics committees participated in 90-minute focus groups. 5 Overall, 51% of KIs said they had heard of the site to access EPC reports and 28% had used material from them. This is very similar to what we found in our current project with four of nine KIs being familiar with EPC reports and/or the journal publications that result from them.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…A similarly designed study in a large academic health care system suggested the same. 18 Members of Pharmacy and Therapeutics committees (pharmacists and physicians from various health systems and organizations) participating in focus groups 34 were asked about their use of AHRQ EPC Program Comparative Effectiveness Reviews (CERs). Only 26% reported using the reviews in their organizations.…”
Section: Types Of Evidence Synthesis Sought By Health Systemsmentioning
confidence: 99%
“…In particular, they wanted training in evaluation of "evidence hierarchies," and wanted online course delivery. 34 In several studies, decisionmakers were interviewed or observed to identify preferences for presentation format. In general, they preferred summaries that were brief, presented in a "graded" format (key messages, executive summary) or presented verbally.…”
Section: Tools For Promoting Use Of Evidence In Health System Decisionsmentioning
confidence: 99%
“…As a result, CER/PCOR evidence is rapidly accumulating in the literature. However, there remains a need to better integrate CER/PCOR evidence into decision making [5][6][7][8][9]. A major limitation may be that potential users of this evidence need to be educated on the strengths and weaknesses of CER and its place within the hierarchy of evidence levels.…”
mentioning
confidence: 99%